PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) BERBANTUAN QUIZZIZ TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VIII SMPN 12 PADANG - Aldo Saprianto; Melisa; Hafizah Delyana; Rina Febriana RF (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematics learning outcomes of eighth grade students of SMPN 12 Padang. This study aims to determine whether student learning outcomes with the implementation of the Think Pair Share (TPS) model are better than the implementation of conventional learning at SMPN 12 Padang. This type of research is an experimental study with a True Experimental design with a posttest-only control group design. This study was conducted with two sample class groups, the first experimental class that applies the TPS model and the second control class that uses the conventional learning model (PBL). The sampling of both samples was carried out using a Random Sampling technique consisting of 9 sample populations. The population of this study was eighth grade students of SMPN 12 Padang. The instrument used in this study was a Post-test in the form of an essay. The test statistics used for hypothesis testing were the t-test, because the two sample classes were not normally distributed. The results of the hypothesis test obtained t_count = 4.7 and t_table = -1.6. Since t_calculated > t_table with a significance level of 0.05, H_0 is rejected, meaning the hypothesis is accepted. Therefore, it can be concluded that the mathematics learning outcomes of eighth-grade students at SMPN 12 Padang using the Think Pair Share (TPS) model are better than those using the Problem Based Learning (PBL) model.